Utilizing Encryption Keys Derived from Immunoaffinity Interactions as a Basis for Potential Security Enhancements - Cowley, Abby; Newland, Ashley; Halámková, Lenka; Manson, Richelle; Morales, Jaleigh; Halámek, Jan (ACS omega, 2025)
Bioaffinity interactions allow antibodies and antigens to bind and were shown to successfully produce cryptographic keys for encryption in this research. This straightforward immune-system-based construct has shown that data obtained from immunoassay interactions may be utilized to create symmetrical key ciphers. The Advanced Encryption Standard (AES), the current standard method to encrypt and decrypt data, was implemented to show that biomolecules from immune systems can be applied to cryptography for security enhancements. When the sender and receiver use identical protocols and component concentrations, the symmetrical key ciphers can be encrypted and decrypted. Variable immunoassay concentrations, pH, temperature, and data point sorting protocols applied to encryption systems will prevent key repetition and alleviate the ability for unauthorized system access, which solves prominent issues in cryptography. This concept can also strengthen cryptographic processes by providing additional security levels of varying complexity using other indirect methods with this nontraditional immunoaffinity approach to current cipher algorithms.